Concept of Productivity Levels in Modeling Sugar Beet Yields - Fetyukhin , Igor; Avdeenko, Aleksei; Avdeenko, Svetlana; Riabtseva, Natalia (KnE Life Sciences, 2021)
Various approaches have been used to model the productive potential of sugar beets under the conditions of unstable moistening of the steppe zone of Russia. This paper considers the general theoretical approach to the functional description of most of the processes of plant growth and development in ontogenesis, as well as of any organism, which is determined by the conversion of bioclimatic resources into the biological mass of plants. Through mathematical modeling, the potential productivity of sugar beets in the absence of limiting factors, with optimal provision of plant life factors, was determined. The second level of modeling sugar beet productivity was performed for the conditions of unstable moistening in the steppe zone of Russia, where soil moisture is a factor limiting the productivity of the crop. To predict productivity in conditions of moisture deficiency, the study used plant organs and soil processes as a model, since they determine the availability of water and nutrients for the plant root system. Given the practical applications of the data for real production conditions, the data obtained in the first and second levels of crop productivity modeling were compared with the actual yield data obtained empirically. The maximum rates of dry matter accumulation for the conditions of the steppe zone of Russia in the absence of limiting factors was not limited to the supply of photosynthetically active radiation (PAR) and could produce up to 16 t/ha of dry matter root crops. With a moisture deficit during the beginning of row closing (from the 45th to the 75th day of the growing season), there was almost no increase in the dry matter of the plant mass, which reduced the potential productivity of sugar beets by 50%. Keywords: crop modeling, sugar beet, potential crop, photosynthesis, moisture supply